1999
DOI: 10.1111/j.1528-1157.1999.tb00911.x
|View full text |Cite
|
Sign up to set email alerts
|

Photic Stimulation: Standardization of Screening Methods

Abstract: Summary: Purpose: Differences in methodology of intermittent photic stimulation within and between countries in Europe make collaborative research and interpretation of results difficult.Method: Experts in the field of photic stimulation from European countries have given an overview of methods used in routine photic stimulation. A consensus meeting was organized in May 1996 in the Netherlands.Results: Methodology, including specification of a photoDuring intermittent photic stimulation (IPS), subtle seizures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(23 citation statements)
references
References 10 publications
1
21
0
1
Order By: Relevance
“…[51]. During IPS in the EEG laboratory, an epileptiform EEG reaction or so-called PPR can be elicited in these patients with the highest prevalence in adolescents.…”
Section: Role Of Photosensitivitymentioning
confidence: 99%
“…[51]. During IPS in the EEG laboratory, an epileptiform EEG reaction or so-called PPR can be elicited in these patients with the highest prevalence in adolescents.…”
Section: Role Of Photosensitivitymentioning
confidence: 99%
“…In particular specific cognitive activities associated with decision making and hand movements and non-specific emotional factors associated with playing (anxiety, excitement) may increase the risk of a seizure (Bureau et al, 2004). In effect, Kasteleijn-Nolst Trenite´et al (1999b) showed that subjects know to have seizures induced by VGs, were more sensitive to playing rather simply to viewing the game under test conditions, and 14% could not be shown to be photosensitive. In daily life, extrinsic non-specific factors such as sleep deprivation, drug or alcohol use, prolonged exposure to the stimulus, may also play a role in reflex seizure occurrence (De Keyser et al, 1984;Zifkin and Inoue, 2004).…”
Section: Photosensitivity: Social Implicationsmentioning
confidence: 99%
“…Takahashi and Tsukahara [29] noted that flicker frequency of 20–15 Hz was most effective in eliciting generalized PPR. Other surveys found that most patients are sensitive between 10 and 30 Hz [30] and peak sensitivity is between 16 and 20 flashes/s [16]. Fisher et al, 2005, reported that frequencies of 15–25 Hz are the most provocative.…”
Section: Discussionmentioning
confidence: 99%